Effect of Mo insertion layers on the magnetoresistance and perpendicular magnetic anisotropy in Ta/CoFeB/MgO junctions - Almasi, H. (AMER INST PHYSICS, 2016)
The effect of a thin Mo dusting layer inserted at the interface of Ta/CoFeB of perpendicular magnetic tunneling junction with MgO barriers was investigated. Unlike thick Mo layers that exhibited a strong (110) crystalline texture, the inserted Mo layer between Ta/CoFeB had little negative influence on the crystallization of CoFe (001), therefore combining the advantages of Mo as a good thermal barrier and Ta as a good boron sink. For optimized Mo dusting thickness, a large tunneling magnetoresistance of 208% was achieved in perpendicular magnetic tunneling junctions with superior thermal stability at 500 degrees C. Published by AIP Publishing.